Analysis of economic data - Koop, Gary (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2009)
Econometrics is concerned with the tasks of developing and applying quantitative or statistical methods to the study and elucidation of economic principles.Analysis of Economic Data teaches methods of data analysis to readers whose primary interest is not in econometrics, statistics or mathematics. It shows how to apply econometric techniques in the context of real-world empirical problems, and adopts a largely non-mathematical approach relying on verbal and graphical intuition. The book covers most of the tools used in modern econometrics research e.g. correlation, regression and extensions for time-series methods and contains extensive use of real data examples and involves readers in hands-on computer work.
Includes bibliographical references and index.
1
Keywords: Econometrics